A PBa-reinforced aramid III nanofiber flame-retardant gas gel and preparation method thereof

Aramid III nanofibers were prepared by deprotonation method and combined with phosphoric acid-catalyzed polybenzoxazine to form a crosslinked longitudinal striped pore structure flame retardant aerogel, which solved the problem of insufficient comprehensive performance of aramid nanofiber composite aerogel in the prior art, and achieved low shrinkage, high mechanical strength, good heat insulation and high flame retardant properties of the aerogel.

CN119529373BActive Publication Date: 2025-04-29SOUTHWEST PETROLEUM UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510104115.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-23
Publication Date
2025-04-29
Estimated Expiration
2045-01-23

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently and easily prepare aramid nanofiber composite aerogels with excellent comprehensive performance in the process flow, especially in terms of thermal insulation, mechanical strength and thermal stability.

Method used

Aramid III nanofibers were prepared by deprotonation method and composited with phosphoric acid-catalyzed granular polybenzoxazine (PBa) to form a crosslinked flame-retardant agel with a crosslinked longitudinal stripe pore structure.

Benefits of technology

It achieves extremely low volume shrinkage, excellent mechanical properties, good thermal insulation and efficient flame retardant properties of aerogels, and is suitable for high-end applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119529373B_ABST
    Figure CN119529373B_ABST
Patent Text Reader

Abstract

The invention discloses a PBa-reinforced aramid III nanofiber flame-retardant gas gel and a preparation method, which belongs to the field of aerogel preparation. The preparation steps include: constructing aramid III nanofibers by a deprotonation method and then preparing aramid III nanofiber gel by protonation, then blending benzoxazine solution and phosphoric acid, and finally freeze-drying to obtain a flame-retardant gas gel. The prepared flame-retardant gas gel is composed of granular polybenzoxazine (PBa) catalyzed by phosphoric acid and a cross-linked aramid III nanofiber skeleton, and has a longitudinal striped pore structure, wherein the granular PBa with phosphoric acid covers the aramid III nanofiber to synergistically construct a continuous and stable flame-retardant skeleton, providing a multi-level flame-retardant structure for it. The flame-retardant gas gel prepared by the present invention has good and stable mechanical properties and excellent flame-retardant and heat-insulating capabilities, and has broad application prospects in the field of flame-retardant and heat-insulating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of aerogel preparation, and in particular to a PBa-reinforced aramid III nanofiber flame-retardant gas gel and a preparation method thereof. The flame-retardant gas gel is composed of phosphoric acid-catalyzed granular polybenzoxazine (PBa) and a cross-linked aramid III nanofiber skeleton, and has a longitudinal stripe pore structure. Background Art

[0002] Aerogel, as a lightweight porous material, has attracted much attention in the field of thermal insulation due to its low density, high porosity and low thermal conductivity. In particular, flame-retardant thermal insulation aerogels not only provide excellent thermal insulation performance, but also increase the safety of the material, making it have broad application prospects in building insulation, aerospace and new energy batteries.

[0003] Aramid III nano aerogel is a new type of material with unique properties. It is composed of ultra-light nanofibers with extremely low density and high porosity. These characteristics make aramid III nano aerogel show great potential in thermal insulation, environmental protection and separation processes. Studies have shown that through different preparation methods, such as wet spinning technology and freeze-drying process. However, aramid III nanofiber aerogel faces the challenge of volume shrinkage during the drying process. This phenomenon will lead to an increase in its density and a decrease in porosity, which in turn affects its performance in high-end applications. The research on aramid III nano aerogel is still in its early stages, and optimizing preparation technology and improving performance are still research hotspots. In the future, this material is expected to play an important role in emerging fields such as intelligent protection, thermal management and separation filtration.

[0004] Polybenzoxazine is a high-performance thermosetting resin that contains benzene and oxazine rings in its structure, so it exhibits excellent mechanical properties and thermal stability. This material has a high carbon residue rate and a high glass transition temperature. The synthesis process of polybenzoxazine involves the reaction of phenolic compounds, primary amine compounds and aldehydes, and there is almost no small molecule release during its curing process, which means that the product has low porosity and near-zero shrinkage. These properties make polybenzoxazine an ideal choice for the preparation of high-performance composite materials, aerospace components, electronic equipment and other fields.

[0005] Patent CN108727639A discloses a preparation method and application of bacterial cellulose / aramid nanofiber composite aerogel. The addition of bacterial cellulose undoubtedly reduces the volume shrinkage of the composite aerogel and improves the mechanical properties of the composite aerogel, but at the same time, the addition of bacterial cellulose also reduces its flame retardant properties, which limits the application of aerogel to a certain extent.

[0006] Patent CN117126453A discloses a hydrophobic and oleophilic aramid nanofiber aerogel and a preparation method thereof. The application degrades aramid fibers by a specific process, prepares the obtained aramid nanofiber dispersion into a hydrogel, performs two solvent exchanges with a specific solvent, and then composites with aqueous polyurethane and freeze-dries it, so that the aramid fibers and polyurethane molecules are cross-linked and entangled to obtain a composite aerogel, which is then immersed in a dispersion containing polydimethylsiloxane (PDMS) and a curing agent, further freeze-dried, and finally obtains a hydrophobic and oleophilic aramid nanofiber aerogel with a special structure through the synergistic effect of various substances. The invention performs two solvent exchanges, which greatly increases the preparation time. At the same time, the heat resistance of the hydrophobic and oleophilic aramid nanofiber aerogel obtained after adding aqueous polyurethane is relatively limited.

[0007] Therefore, the field of aerogel materials faces a major challenge, which is how to prepare aramid nanofiber composite aerogels with excellent comprehensive performance in an efficient and simple way. This requires not only innovation in the process flow, but also in-depth research on the microstructure of the material to ensure the best results in terms of thermal insulation, mechanical strength and thermal stability. Breaking through this difficulty will bring great impetus to the development and application of new materials, and has important theoretical and practical significance. Summary of the invention

[0008] The present invention aims to solve the problem that pure aramid III nanofiber aerogel cannot simultaneously take into account mechanical properties, thermal insulation properties, and flame retardant properties. A method for preparing a PBa-reinforced aramid III nanofiber flame retardant gas gel is provided, which is carried out according to the following steps:

[0009] S1. Potassium hydroxide, deionized water, and aramid III fibers are placed in dimethyl sulfoxide, and then stirred at room temperature for 48 hours at a stirring speed of 400 r / min to deprotonate the aramid III nanofibers to obtain a red aramid III nanofiber solution;

[0010] S2, uniformly mixing the deionized water and the aramid III nanofiber solution and stirring at a speed of 400 r / min for 1 h to obtain the aramid III nanofiber colloid, and then filtering the aramid III nanofiber colloid with anhydrous ethanol and deionized water in a microporous filter to complete solvent replacement to obtain the aramid III nanofiber gel;

[0011] S3, uniformly mixing the obtained aramid III nanofiber gel and the benzoxazine solution at room temperature, and simultaneously dropping a phosphoric acid aqueous solution for ring-opening polymerization of benzoxazine, and finally obtaining a polybenzoxazine / aramid III nanofiber composite gel;

[0012] S4. Pour the obtained polybenzoxazine / aramid III nanofiber composite gel into a 2×2×2 cm mold, and then place the mold in a -60°C cold trap for directional freezing for 2 hours to obtain the polybenzoxazine / aramid III nanofiber composite cryogel. After demolding the polybenzoxazine / aramid III nanofiber composite cryogel, freeze-dry it in a freeze dryer at -60°C for 48 hours to obtain the polybenzoxazine / aramid III nanofiber composite aerogel, which is PBa-reinforced aramid III nanofiber flame-retardant gas gel.

[0013] As a further improvement of the present invention, the mass ratio of potassium hydroxide to aramid III fiber in step S1 is 3:2; the mass ratio of dimethyl sulfoxide to deionized water is 24:1; the concentration of aramid III nanofiber solution is 10 g / L, and the viscosity is 10.5 mPa·s / 25°C.

[0014] As a further improvement of the present invention, the volume ratio of the deionized water and the aramid III nanofiber solution when mixed in step S2 is 3:2; the solution is filtered and washed twice with anhydrous ethanol and three times with deionized water, and the pore size of the microporous filter is 2.2 μm.

[0015] As a further improvement of the present invention, the aramid III nanofiber gel and the benzoxazine solution in step S3 are stirred and mixed at a solid content ratio of 10: (1-5) at a speed of 100 r / min for 10 min; the benzoxazine is water-soluble benzoxazine, whose mass fraction is 40.1% and the viscosity is 12.1 mPa·s / 25°C, the mass fraction of the phosphoric acid aqueous solution is 85%, and the solid content ratio of the benzoxazine solution to the phosphoric acid aqueous solution is 10: (3-7).

[0016] As a further improvement of the present invention, the flame-retardant gas gel is composed of granular polybenzoxazine (PBa) catalyzed by phosphoric acid and a cross-linked aramid III nanofiber skeleton, and has a longitudinal striped pore structure.

[0017] As a further improvement of the present invention, the PBa-reinforced aramid III nanofiber flame-retardant gas gel has a maximum diameter of 30 nm and a minimum diameter of 8 nm, and a size of the granular polybenzoxazine of 1.402±0.761 μm.

[0018] As a further improvement of the present invention, the PBa-reinforced aramid III nanofiber flame-retardant gas gel has a specific surface area of ​​28.4 cm 2 / g, density is 0.13 g / cm 3 The porosity is 94.7%, the compressive strength is 1.81 MPa, the carbon residue rate at 700 °C is 42.1%, and the final value of the total heat release rate is 2.6 MJ / m 2 , thermal conductivity is 0.0256 W / m·K.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] (1) The present invention prepares aramid III nanofibers by a deprotonation method. First, the hydrogen in the amide group is occupied by the solvent system to generate negatively charged polymer chains. Then, the hydrogen bond network between the aramid III polymer chains is broken due to electrostatic repulsion, and the macroscopic fibers are split into individual nanofibers with a diameter of 8-30 nm. Finally, the aramid III nanofiber solution exists stably under the balanced action of electrostatic repulsion, π-π stacking and van der Waals forces.

[0021] (2) The present invention prepares a PBa-reinforced aramid III nanofiber flame-retardant gas gel. Benzoxazine forms a macromolecular chain through phosphoric acid-catalyzed ring-opening polymerization. At the same time, it undergoes physical crosslinking with aramid III nanofibers, giving the polybenzoxazine / aramid III nanofiber composite aerogel a complex skeleton network. The polybenzoxazine makes the polybenzoxazine / aramid III nanofiber composite aerogel have an extremely low volume shrinkage rate and a specific surface area of ​​28.4 cm 2 / g, density is 0.13 g / cm 3 , the porosity is 94.7%; at the same time, stable and excellent mechanical properties are obtained, and its compressive strength can reach 1.81MPa.

[0022] (3) The PBa-reinforced aramid III nanofiber flame-retardant gas gel prepared by the present invention forms a longitudinal striped pore structure, which provides a good thermal insulation configuration for the aerogel, and thus has an extremely low thermal conductivity of 0.0256 W / m·K, indicating its excellent thermal insulation performance and can achieve high-efficiency thermal insulation.

[0023] (4) The PBa-reinforced aramid III nanofiber flame retardant gas gel prepared by the present invention has excellent flame retardant properties. Due to the large amount of nitrogen elements in aramid III nanofibers and benzoxazine and the phosphorus element in phosphoric acid, the polybenzoxazine / aramid III nanofiber composite aerogel has excellent flame retardant properties. The residual amount of thermal decomposition at 700°C can still reach 42.1%, and it extinguishes immediately when away from the fire in the vertical combustion test, and the final value of the total heat release rate is 2.6 MJ / m 2 . BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. The drawings in the following description are merely embodiments and comparative examples of the present invention.

[0025] Figure 1 It is a schematic diagram of the preparation process of a method for preparing a PBa-reinforced aramid III nanofiber flame-retardant gas gel of the present invention;

[0026] Figure 2 a), b), and c) are digital photos of aramid III nanofiber solution, aramid III nanofiber gel, and benzoxazine solution used in the preparation of a PBa-reinforced aramid III nanofiber flame-retardant gas gel;

[0027] Figure 3 a) and b) are scanning electron microscope (SEM) and energy dispersive spectrometer (EDS) images of the polybenzoxazine / aramid III nanofiber composite aerogel prepared in Example 1, respectively;

[0028] Figure 4 a), b), and c) are scanning electron microscope images of the longitudinal stripe pore structure inside the polybenzoxazine / aramid III nanofiber composite aerogel prepared in Example 1 at different magnifications;

[0029] Figure 5 This is a thermogravimetric graph of Example 1;

[0030] Figure 6 This is a digital photo of the vertical combustion test of Example 1;

[0031] Figure 7 The thermal conductivity bar graphs of Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 are shown;

[0032] Figure 8 The compressive stress-strain curves of Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 are shown. DETAILED DESCRIPTION

[0033] The present invention provides a method for preparing a PBa-reinforced aramid III nanofiber flame-retardant gas gel. In order to make the purpose, technical scheme and advantages of the present invention clearer and more specific, the present invention is further described in conjunction with specific embodiments and drawings.

[0034] Example 1

[0035] like Figure 1 As shown, the specific steps of the preparation method of the PBa-reinforced aramid III nanofiber flame-retardant gas gel of the present invention are as follows:

[0036] Step 1: 7.5 g potassium hydroxide, 5 g aramid III fiber, 20 ml deionized water and 480 ml dimethyl sulfoxide were mixed, and stirred at a speed of 400 r / min for 48 h to obtain a 10 g / L aramid III nanofiber solution;

[0037] Step 2: Add 600 ml of deionized water to 200 ml of the aramid III nanofiber solution and stir at a speed of 400 r / min for 1 hour, and then filter and wash with anhydrous ethanol for 2 times and deionized water for 3 times to obtain the aramid III nanofiber gel;

[0038] Step 3: The aramid III nanofiber gel and the benzoxazine solution are uniformly mixed at room temperature in a solid content ratio of 10:5, and a phosphoric acid aqueous solution is added dropwise for ring-opening polymerization of benzoxazine, wherein the solid content ratio of the benzoxazine solution to the phosphoric acid aqueous solution is 10:7, and finally a polybenzoxazine / aramid III nanofiber composite gel is obtained;

[0039] Step 4: Pour the obtained polybenzoxazine / aramid III nanofiber composite gel into a 2*2*2 cm mold, and then place the mold in a -60°C cold trap for directional freezing for 2 hours to obtain the polybenzoxazine / aramid III nanofiber composite cryogel. After the polybenzoxazine / aramid III nanofiber composite cryogel is demolded, it is freeze-dried in a freeze dryer at a temperature of -60°C for 48 hours to obtain the polybenzoxazine / aramid III nanofiber composite aerogel, i.e., PBa-reinforced aramid III nanofiber flame-retardant gas gel.

[0040] The aramid III nanofiber solution, aramid III nanofiber gel, and benzoxazine solution prepared and used in Example 1 were observed, and the results were as follows: Figure 2 a) left, Figure 2 b) In Figure 2 c) As shown on the right.

[0041] The polybenzoxazine / aramid III nanofiber composite aerogel prepared in Example 1 was analyzed by scanning electron microscopy and energy spectrum. The results are as follows Figure 3 a) and Figure 3 b). Figure 3 It shows that polybenzoxazine was successfully polymerized and coated with aramid III m fiber.

[0042] The interior of the polybenzoxazine / aramid III nanofiber composite aerogel prepared in Example 1 was observed by scanning electron microscopy. The aerogel had an orderly arranged longitudinal stripe pore structure. Figure 4 a), b), and c).

[0043] The polybenzoxazine / aramid III nanofiber composite aerogel prepared in Example 1 was subjected to thermogravimetric analysis, and the results are as follows: Figure 5 shown.

[0044] The polybenzoxazine / aramid III nanofiber composite aerogel prepared in Example 1 was subjected to a vertical combustion test, and the results are as follows: Figure 6 shown.

[0045] Comparative Examples 1-2

[0046] Comparative Examples 1 to 2 provide a method for preparing a PBa-reinforced aramid III nanofiber flame-retardant gas gel. Compared with Example 1, the difference is that in step 3, the solid content ratios of the aramid III nanofiber gel and the benzoxazine solution are 10:2 and 10:1, respectively. The rest is the same as Example 1 and will not be repeated here.

[0047] Comparative Example 3

[0048] Comparative Example 3 provides a method for preparing a PBa-reinforced aramid III nanofiber flame-retardant gas gel. Compared with Example 1, the difference is that step 3 is omitted, and step 4 is the same as Example 1 without polybenzoxazine and phosphoric acid to obtain pure aramid III nanofiber aerogel.

[0049] Comparative Examples 4-5

[0050] Comparative Examples 4-5 provide a method for preparing a PBa-reinforced aramid III nanofiber flame-retardant gas gel. Compared with Example 1, the difference is that in step 3, the solid content ratios of the benzoxazine solution and the phosphoric acid aqueous solution are 10:3 and 10:5, respectively.

[0051] The flame retardant properties of the flame retardant gas gels prepared in Example 1 and Comparative Examples 2 to 5 were tested using an iCone classic cone calorimeter from FTT (35 kWm -2 The test results are shown in Table 1:

[0052] Table 1 Flame retardant performance test results of flame retardant gas gel

[0053]

[0054] As shown in Table 1, Example 1 and Comparative Examples 1-2, the increase in the benzoxazine content leads to a decrease in the final value of the total heat release rate (THR), the average heat release rate (AvHRR), and the peak heat release rate (PHRR) of the flame-retardant gas gel. This is related to the formation of a multi-stage flame-retardant configuration by polymerizing benzoxazine and coating the aramid III nanofibers. When the polybenzoxazine is heated, it begins to carbonize to form protection, while releasing non-flammable gas to dilute oxygen and further retardant.

[0055] By comparing Example 1 with Comparative Examples 4-5, it is found that the increase in the content of catalyst phosphoric acid greatly improves the flame retardant properties of the flame retardant gas gel. This is attributed to the fact that during combustion, the phosphorus compound decomposes into a non-flammable phosphoric acid liquid film, and the phosphoric acid is further dehydrated to form metaphosphoric acid, which is then polymerized into polymetaphosphoric acid. The strong acidic dehydration effect of the phosphoric acid coating layer and the polymetaphosphoric acid dehydrates and carbonizes the polymer to form a carbon film that isolates the air, thereby enhancing the flame retardant effect.

[0056] The thermal conductivity of the flame-retardant gas gel prepared in Example 1 and Comparative Examples 1 to 3 was tested using a multifunctional thermal conductivity tester. The test results are as follows: Figure 7 As shown, the thermal conductivity of Example 1 and Comparative Examples 1 to 3 are 0.0256 W / m·K, 0.0211 W / m·K, 0.0191 W / m·K, and 0.0190 W / m·K, respectively, which indicates that the thermal conductivity of the flame-retardant gas gel is slightly increased, but still has excellent thermal insulation ability. This is related to the addition of polybenzoxazine, which forms a denser network skeleton on the aramid III nanofibers, resulting in an increase in thermal conductivity.

[0057] The mechanical properties of Example 1 and Comparative Examples 1 to 3 were tested using a universal tensile testing machine. The results are as follows: Figure 8 As shown in the figure, there are significant differences, and their compressive strengths are 1.81MPa, 1.49MPa, 0.65MPa and 0.11MPa, respectively; acid-catalyzed ring-opening polymerization forms macromolecular chains, and at the same time, they are physically cross-linked with aramid III nanofibers, giving the polybenzoxazine / aramid III nanofiber composite aerogel a complex and dense skeleton network, greatly enhancing the mechanical properties of the flame-retardant gas gel.

[0058] In summary, the present invention uses aramid III nanofibers, benzoxazine, and phosphoric acid as raw materials to successfully prepare a PBa-enhanced aramid III nanofiber flame-retardant gas gel. The aerogel is composed of granular polybenzoxazine (PBa) catalyzed by phosphoric acid and a cross-linked aramid III nanofiber skeleton, and has a longitudinal striped pore structure, wherein the granular PBa with phosphoric acid covers the aramid III nanofibers to synergistically construct a continuous and stable flame-retardant skeleton, providing a multi-level flame-retardant structure. Aramid III nanofibers and polybenzoxazine molecular chains contain a large amount of nitrogen elements, and a large amount of non-combustible gas is produced after combustion to dilute the oxygen in the air. At the same time, the formation of polyphosphoric acid during the heating process helps to further prevent the combustion of the material. In addition, its strong network skeleton not only enhances the mechanical properties of the composite aerogel, but also helps to prevent the generation of thermal convection, thereby greatly improving the thermal insulation capacity of the polybenzoxazine / aramid III nanofiber composite aerogel. In short, a PBa-enhanced aramid III nanofiber flame-retardant gas gel and preparation method provide a feasible solution to the challenge of flame retardancy and thermal insulation.

Claims

1. A method for preparing a PBa-reinforced aramid III nanofiber flame-retardant gel, characterized in that: The following steps are involved: S1. Potassium hydroxide, deionized water, and aramid III fibers are placed in dimethyl sulfoxide, and then stirred at room temperature for 48 hours at a stirring speed of 400 r / min to deprotonate the aramid III fibers and obtain a red aramid III nanofiber solution; S2, uniformly mixing the deionized water and the aramid III nanofiber solution and stirring at a speed of 400 r / min for 1 h to obtain the aramid III nanofiber colloid, and then filtering the aramid III nanofiber colloid with anhydrous ethanol and deionized water in a microporous filter to complete solvent replacement to obtain the aramid III nanofiber gel; S3, uniformly mixing the obtained aramid III nanofiber gel and the benzoxazine solution at room temperature, and simultaneously dropping a phosphoric acid aqueous solution for ring-opening polymerization of benzoxazine, and finally obtaining a polybenzoxazine / aramid III nanofiber composite gel; S4. Pour the obtained polybenzoxazine / aramid III nanofiber composite gel into a 2×2×2 cm mold, and then place the mold in a -60°C cold trap for directional freezing for 2 hours to obtain the polybenzoxazine / aramid III nanofiber composite cryogel. After demolding the polybenzoxazine / aramid III nanofiber composite cryogel, freeze-dry it in a freeze dryer at a temperature of -60°C for 48 hours to obtain the polybenzoxazine / aramid III nanofiber composite aerogel, i.e., PBa-reinforced aramid III nanofiber flame-retardant gas gel.

2. The method for preparing a PBa-reinforced aramid III nanofiber flame-retardant gel according to claim 1, characterized in that: The mass ratio of potassium hydroxide to aramid III fiber in S1 is 3:2; the mass ratio of dimethyl sulfoxide to deionized water is 24:1; the concentration of aramid III nanofiber solution is 10 g / L, and the viscosity is 10.5 mPa·s / 25°C.

3. The method for preparing a PBa-reinforced aramid III nanofiber flame-retardant gel according to claim 1, characterized in that: The volume ratio of the deionized water and the aramid III nanofiber solution in the S2 when mixed is 3:2; the solution is filtered and washed twice with anhydrous ethanol and three times with deionized water; the pore size of the microporous filter is 2.2 μm.

4. The method for preparing a PBa-reinforced aramid III nanofiber flame-retardant gel according to claim 1, characterized in that: The aramid III nanofiber gel in S3 and the benzoxazine solution are stirred at a solid content ratio of 10:5 at a speed of 100 r / min for 10 minutes; the benzoxazine is water-soluble benzoxazine, whose mass fraction is 40.1% and viscosity is 12.1 mPa·s / 25°C, the mass fraction of the phosphoric acid aqueous solution is 85%, and the solid content ratio of the benzoxazine solution to the phosphoric acid aqueous solution is 10:

7.

5. A PBa-reinforced aramid III nanofiber flame-retardant gel, characterized in that: The method for preparing the PBa-reinforced aramid III nanofiber flame-retardant gas gel according to any one of claims 1 to 4 is used to obtain the gel.

6. The PBa-reinforced aramid III nanofiber flame-retardant gel according to claim 5, characterized in that: The flame-retardant gas gel is composed of granular polybenzoxazine catalyzed by phosphoric acid and a cross-linked aramid III nanofiber skeleton, and has a longitudinal stripe pore structure.

7. The PBa-reinforced aramid III nanofiber flame-retardant gel according to claim 6, characterized in that: The diameter of the aramid III nanofiber is 30 nm at the maximum and 8 nm at the minimum, and the size of the granular polybenzoxazine is 1.402±0.761 μm.

8. The PBa-reinforced aramid III nanofiber flame-retardant gel according to claim 5, characterized in that: The flame-retardant gas gel has a specific surface area of ​​28.4 cm 2 / g, density is 0.13 g / cm 3 The porosity is 94.7%, the compressive strength is 1.81 MPa, the carbon residue rate at 700 °C is 42.1%, and the final value of the total heat release rate is 2.6 MJ / m 2 , thermal conductivity is 0.0256 W / m·K.

Citation Information

Patent Citations

  • Preparation method and application of bacterial cellulose / aramid nano fiber composite aerogel

    CN108727639A

  • Hydrophobic oleophylic aramid nanofiber aerogel and preparation method thereof

    CN117126453A

  • Kevlar-polybenzoxazine aerogel and preparation method thereof

    CN119391040A